Association between Life’s Essential 8 and mortality in urinary incontinence among US female adults - Xiaoping Xu; Ruiqian Liu (Journal of Obstetrics and Gynaecology)
Background Urinary incontinence (UI) may be associated with cardiovascular disease. Life’s Essential 8 (LE8), a recently updated measure of cardiovascular health (CVH), has been investigated for its association with all-cause and cardiovascular mortality among US female adults with UI.Methods This population-based retrospective cohort study utilised data from 6314 US female adults aged ≥20 years with UI (weighted population: 4.14 million) derived from the National Health and Nutrition Examination Survey (NHANES) 2005–2018, along with their linked mortality data up to December 2019. The LE8 metric, ranging from 0 to 100, was categorised into low, moderate, and high levels. UI status was determined by self-report. Multivariable Cox proportional hazards regression models were employed to assess the associations between LE8 and both all-cause and cardiovascular disease (CVD) mortality. A stratified analysis and sensitivity analysis were also conducted.Results During a median follow-up period of 92 months (with a maximum of 180 months) among US adult females with UI, 684 all-cause deaths were recorded, including 169 deaths attributable to cardiovascular disease. A 10-point increase in the LE8 score was associated with a 14% reduction in the risk of all-cause mortality (hazard ratio [HR], 0.86; 95% confidence interval [CI], 0.79–0.93) and a 17% reduction in the risk of CVD mortality (HR, 0.83; 95% CI, 0.71–0.97). Physical activity has the most significant effect. In the stratified subgroups and sensitivity analyses, the results remained robust.Conclusions An elevated LE8 score was independently correlated with reduced risks of all-cause and cardiovascular mortality among US female adults with UI. Future prospective studies are required to further strengthen our findings.